Rapamycin Enhances Mitophagy and Attenuates Apoptosis After Spinal Ischemia-Reperfusion Injury - Li, Qiang; Gao, Shane; Kang, Zhanrong; Zhang, Meiyan; Zhao, Xin; Zhai, Yu; Huang, Jianming; Yang, Guo-Yuan; Sun, Wanju; Wang, Jian (Frontiers in Neuroscience, 2018)
The spinal cord is extremely vulnerable to ischemia-reperfusion (I/R) injury, and the mitochondrion is the most crucial interventional target. Rapamycin can promote autophagy and exert neuroprotective effects in several diseases of the central nervous system. However, the impact of rapamycin via modulating mitophagy and apoptosis after spinal cord ischemia-reperfusion injury remains unclear. This study was undertaken to investigate the potential role of rapamycin in modulating mitophagy and mitochondria-dependent apoptosis using the spinal cord ischemia-reperfusion injury (SCIRI) mouse model. We found that rapamycin significantly (p < 0.05) enhanced mitophagy by increasing the translocation of p62 and Parkin to the damaged mitochondria in the mouse spinal cord injury model. At the same time, rapamycin significantly (p < 0.05) decreased mitochondrial apoptosis related protein (Apaf-1, Caspase-3, Caspase-9) expression by inhibiting Bax translocation to the mitochondria and the release of the cytochrome c from the mitochondria. After 24 h following SCIRI, rapamycin treatment reduced the TUNEL+ cells in the spinal cord ischemic tissue and improved the locomotor function in these mice. Our results therefore demonstrate that rapamycin can improve the locomotor function by promoting mitophagy and attenuating SCIRI -induced apoptosis, indicating its potential therapeutic application in a spinal cord injury.